Strategi Peningkatan Kepuasan Konsumen melalui Kualitas Produk dan Fasilitas - Anindia, Parmadita (KINERJA: Jurnal Manajemen Organisasi dan Industri, 2024)
Modern business developments show that the success of a company depends not only on quality products, but also on the overall consumer experience. Product quality and facilities are key factors that can shape the level of consumer satisfaction. This research aims to explore effective strategies in increasing consumer satisfaction through improving product quality and facilities. With a deep understanding of the impact of both, companies can design more appropriate strategies to meet consumer expectations. The research method involves quantitative analysis to assess consumer perceptions of product and facility quality. Consumer surveys, interviews, and statistical data analysis are used to construct a comprehensive picture of the relationships between these variables. This research reveals that strategies to increase consumer satisfaction that focus on improving product quality and facilities provide a significant positive impact. Business decisions informed by the results of this research can help companies optimize their resources to achieve competitive advantage.